2022
DOI: 10.1111/ijfs.15722
|View full text |Cite
|
Sign up to set email alerts
|

Processing properties of yogurt as affected by the EPS produced by Leuconostoc mesenteroides XR1

Abstract: The aim of this study was to examine the fermentation characteristics of a novel Leuconostoc mesenteroides strain (XR1) and to investigate the effect of XR1 exopolysaccharides (EPS) on the microstructure, texture and rheological properties of yoghurt. The novel Leuconostoc mesenteroides strain (XR1) was isolated from wild kefir grains obtained from Xinjiang Province. The results showed that XR1 had good EPS production capacity and favourable fermentation performance. The addition of XR1 EPS to fermented milk e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…mesenteroides S81 appeared spheroidal or ellipsoidal structural features ( Taylan et al, 2019 ), and EPS from Leu. mesenteroides XR1 was granular with uniform distribution ( Wang et al, 2022 ). These results fully proved that the microstructure of EPSs was strain-specific, even though in the same genus.…”
Section: Resultsmentioning
confidence: 99%
“…mesenteroides S81 appeared spheroidal or ellipsoidal structural features ( Taylan et al, 2019 ), and EPS from Leu. mesenteroides XR1 was granular with uniform distribution ( Wang et al, 2022 ). These results fully proved that the microstructure of EPSs was strain-specific, even though in the same genus.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the milk viscosity is due to polysaccharides produced by lactic acid bacteria in the fermentation process . CPSs and/or EPS produced by lactic acid bacteria are able to improve the water retention capacity and thus viscoelastic properties of fermented milk . Moreover, the protein–polysaccharide interactions in fermented milk can enhance the formation of a complex network gel structure, improving the product texture .…”
Section: Results and Discussionmentioning
confidence: 99%
“…35 CPSs and/ or EPS produced by lactic acid bacteria are able to improve the water retention capacity and thus viscoelastic properties of fermented milk. 36 Moreover, the protein−polysaccharide interactions in fermented milk can enhance the formation of a complex network gel structure, improving the product texture. 37 These data suggested that cow milks fermented with HG-R7970-3 are likely to have better technological properties compared with those fermented by Probio-M9.…”
Section: Hg-r7970-3 Improves the Physicochemical Properties And Lacto...mentioning
confidence: 99%
“…Some prior studies have investigated the functional properties of the exopolysaccharides (EPSs) produced by L. mesenteroides [3,7,[13][14][15][16][17][18][19][20][21][22]. Nonetheless, little research has been carried out on the structural features and immunostimulatory potential of the extracellular polymer that L. mesenteroides (201607) produces [23].…”
Section: Introductionmentioning
confidence: 99%